The Effect of Conservation Agriculture and Environmental Factors on CO2 Emissions in a Rainfed Crop Rotation - Carbonell-Bojollo, R. (2020)
There are many factors involved in the release of CO2 emissions from the soil, such as the type of soil management, the soil organic matter, the soil temperature and moisture conditions, crop phenological stage, weather conditions, residue management, among others. This study aimed to analyse the influence of these factors and their interactions to determine the emissions by evaluating the environmental cost expressed as the kg of CO2 emitted per kg of production in each of the crops and seasons studied. For this purpose, a field trial was conducted on a farm in Seville (Spain). The study compared Conservation Agriculture, including its three principles (no-tillage, permanent soil cover, and crop rotations), with conventional tillage. Carbon dioxide emissions measured across the four seasons of the experiment showed an increase strongly influenced by rainfall during the vegetative period, in both soil management systems. The results of this study confirm that extreme events of precipitation away from the normal means, result in episodes of high CO2 emissions into the atmosphere. This is very important because one of the consequences for future scenarios of climate change is precisely the increase of extreme episodes of precipitation and periods extremely dry, depending on the area considered. The total of emission values of the different plots of the study show how the soils under the conventional system (tillage) have been emitting 67% more than soils under the conventional agriculture system during the 2010/11 campaign and 25% for the last campaign where the most appreciable differences are observed.